Digital health and patient data : empowering patients in the healthcare ecosystem - Choun, Disa; Petre, Anca (New York : Productivity Press, 2022)
Patients with unmet needs will continue to increase as no viable nor adequate treatment exists. Meanwhile, healthcare systems are struggling to cope with the rise of patients with chronic diseases, the ageing population and the increasing cost of drugs. What if there is a faster and less expensive way to provide better care for patients using the right digital solutions and transforming the growing volumes of health data into insights? The increase of digital health has grown exponentially in the last few years. Why is there a slow uptake of these new digital solutions in the healthcare and pharmaceutical industries? One of the key reasons is that patients are often left out of the innovation process. Their data are used without their knowledge, solutions designed for them are developed without their input and healthcare professionals refuse their expertise. This book explores what it means to empower patients in a digital world and how this empowerment will bridge the gap between science, technology and patients. All these components need to co-exist to bring value not only to the patients themselves but to improve the healthcare ecosystem. Patients have taken matters into their own hands. Some are equipped with the latest wearables and applications, engaged in improving their health using data, empowered to make informed decisions and ultimately are experts in their disease(s). They are the e-patients. The other side of the spectrum are patients with minimal digital literacy but equally willing to donate their data for the purpose of research. Finding the right balance when using digital health solutions becomes as critical as the need to develop a disease-specific solution. For the first time, the authors look at healthcare and technologies through the lens of patients and physicians via surveys and interviews in order to understand their perspective on digital health, analyse the benefits for them, explore how they can actively engage in the innovation process, and identify the threats and opportunities the large volumes of data create by digitizing healthcare. Are patients truly ready to know everything about their health? What is the value of their data? How can other stakeholders join the patient empowerment movement? This unique perspective will help us re-design the future of healthcare - an industry in desperate need for a change.
OCLC-licensed vendor bibliographic record.
Keywords: Patient advocacy; Medical informatics; BUSINESS & ECONOMICS / Information Management